2016
DOI: 10.1016/j.nimb.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Geant4 Monte Carlo simulation of absorbed dose and radiolysis yields enhancement from a gold nanoparticle under MeV proton irradiation

Abstract: International audienceGold nanoparticles have been reported as a possible radio-sensitizer agent in radiation therapy due totheir ability to increase energy deposition and subsequent direct damage to cells and DNA within theirlocal vicinity. Moreover, this increase in energy deposition also results in an increase of the radiochemicalyields. In this work we present, for the first time, an in silico investigation, based on the general purposeMonte Carlo simulation toolkit Geant4, into energy deposition and radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 33 publications
8
84
0
Order By: Relevance
“…Overall, the free radical production should be more sensitive to the physical interaction model and production threshold used. The initial free radical production is directly proportional to the dose deposition, or equivalently to the secondary electron production (Tran et al 2016). As Tran et al demonstrated, the time evolution of the distribution suggests that the free radicals on average stay in their initial positions.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, the free radical production should be more sensitive to the physical interaction model and production threshold used. The initial free radical production is directly proportional to the dose deposition, or equivalently to the secondary electron production (Tran et al 2016). As Tran et al demonstrated, the time evolution of the distribution suggests that the free radicals on average stay in their initial positions.…”
Section: Discussionmentioning
confidence: 98%
“…Tran et al . investigated the production of molecular species around gold nanoparticles (GNP) using Geant4‐DNA.…”
Section: Review Of Geant4‐dna‐based Water Radiolysis Simulationsmentioning
confidence: 99%
“…While this is sufficient for modeling many macroscale radiobiological effects, there are cases where modeling the direct damage alone cannot explain experimental observations. For example, there are indications that ROS play a major role in the enhancement of proton radiotherapy by high Z metallic nanoparticles …”
Section: Introductionmentioning
confidence: 99%
“…Tran et al simulated a spherical gold nanoparticle of 50 nm diameter in an environment of water and irradiated by protons with energies between 2 and 170 MeV (21). Based on the results of their research, nanoparticle improves the dose in that area.…”
Section: The Impact Of Gnps On Primitive Dose Profilementioning
confidence: 99%
“…Walzlein et al (8) made MC simulations, using the track structure code TRAX to investigate a possible dose enhancement effect by proton or electron irradiation in the vicinity of nanoparticles consisting of different high Z atomic materials. Tran et al (21) presented an in silico investigation, on the basis of the general purpose MC simulation toolkit Geant4, into energy deposition and radical species production around a spherical GNPs 50 nm in diameter via proton irradiation.…”
Section: Introductionmentioning
confidence: 99%